The role of soil chemistry and plant neighbourhoods in structuring fungal communities in three Panamanian rainforests. (May 2017) - Schappe, Tyler; Albornoz, Felipe E.; Turner, Benjamin L.; Neat, Abigail; Condit, Richard; Jones, F. Andrew
Summary: Fungi play critical roles in ecosystem processes and interact with plant communities in mutualistic, pathogenic, and commensal ways. Fungal communities are thought to depend on both associated tree communities and soil properties. However, the relative importance of the biotic and abiotic drivers of soil fungal community structure and diversity in lowland tropical forests remains poorly understood. We examined the community structure of trees and fungi at different levels of phosphorus (0·17–16·3 mg kg −1 ) in moist tropical forests in Panama. We predicted that arbuscular mycorrhizal (AM) fungal composition would be more strongly associated with soil properties than with local tree communities while the composition of other fungal clades would be more strongly correlated with local tree communities than soil properties. We also predicted that fungal operational taxonomic unit (OTU) richness would be negatively correlated with soil fertility and positively correlated with tree species diversity within and among forests. We characterized soil chemistry, fine root biomass, and sequenced the ITS1 barcode region to describe fungal community composition from 70 soil cores across three 1‐ha tropical rainforest sites in Panama. The sites vary in soil chemistry, including P, and in tree species community composition, but experience similar annual rainfall. AM fungal community composition was partially correlated with soil chemistry ( r  = 0·32, P  ≤ 0·001), but not with local tree communities, while non‐AM fungal communities were nearly equally correlated with soil chemistry (Partial Mantel test, r  = 0·38, P  ≤ 0·001) as with tree communities ( r  = 0·36, P  ≤ 0·001). Linear models showed that AM OTU richness was not explained by any independent variable. For non‐AM fungi, phosphorus, pH, and soil moisture better predicted OTU richness across all cores than other biotic and abiotic factors. Synthesis . Our results show that AM fungal structure is driven primarily by soil chemistry. For non‐AM fungi, soil properties and the local tree community can play a joint role in structuring communities. Furthermore, we found that more diverse local tree communities did not harbour more fungal species. Our results suggest that soil properties act as an environmental filter for both trees and fungi, setting the stage for interactions between the two. Abstract : Our results show that AM fungal structure is driven primarily by soil chemistry. For non‐AM fungi, soil properties and the local tree community can play a joint role in structuring communities. Furthermore, we found that more diverse local tree communities did not harbour more fungal species. Our results suggest that soil properties act as an environmental filter for both trees and 4 fungi, setting the stage for interactions between the two.